Open Data in Southeast Asia Towards Economic Prosperity, Government Transparency, and Citizen Participation in the ASEAN - Stagars, Manuel (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This book explores the power of greater openness, accountability, and transparency in digital information and government data for the nations of Southeast Asia. The author demonstrates that, although the term "open data" seems to be self-explanatory, it involves an evolving ecosystem of complex domains. Through empirical case studies, this book explains how governments in the ASEAN may harvest the benefits of open data to maximize their productivity, efficiency and innovation. The book also investigates how increasing digital divides in the population, boundaries to civil society, and shortfalls in civil and political rights threaten to arrest open data in early development, which may hamper post-2015 development agendas in the region. With robust open data policies and clear roadmaps, member states of the ASEAN can harvest the promising opportunities of open data in their particular developmental, institutional and legal settings. Governments, policy makers, entrepreneurs and academics will gain a clearer understanding of the factors that enable open data from this timely research. Manuel Stagars is a senior researcher at Singapore-ETH Centre (SEC), a research campus in Singapore of the Swiss Federal Institute of Technology (ETH). Manuel leads the project ASEAN+Database at SEC, creating an open data platform from ASEAN member countries, China, and India. He is focusing on technological and institutional aspects of open data, big data, and data policy. An economist by training and a global serial entrepreneur for over a decade, he is also supporting start-ups as an angel investor and is advising corporate and private clients. Manuel studied at the London School of Economics (LSE, UK), and he is a Chartered Financial Analyst (CFA), Chartered Alternative Investment Analyst (CAIA), and Energy Risk Professional (ERP).